Association between human papillomavirus infection or immunization and risk for rheumatoid arthritis - Yang, Guangxia; Ren, Zeqin; Wang, Kai (Frontiers in Immunology, 2023)
Human papillomavirus (HPV) is a virus primarily transmitted through sexual contact. Little is known about the association between HPV infection or immunization and risk for rheumatoid arthritis (RA). The purpose of this study was to evaluate whether HPV infection or immunization is related to the?risk for RA in adults. Data were obtained from the 2007-2016 National Health and Nutrition Examination Survey (NHANES). We developed three independent multivariate logistic regression models to evaluate the association between HPV infection or immunization risk for RA in adults. Finally, we analyzed 15677 and 8944 subjects, respectively. In all models, HPV infection was positively associated with increased prevalence of RA in adults aged 18-59 years, with the highest value of the ratio (OR) in model 2 (After weighting: OR 1.095, 95% CI 1.092, 1.097), whereas HPV immunization significantly reduced the prevalence of RA in adults aged 18-59 years, with the lowest OR in model C (After weighting: OR 0.477, 95% CI 0.472, 0.481). These associations persisted after correction for confounders such as age, sex, race, education level, marital status, smoking, diabetes, hypertension, hyperlipidemia, and BMI. In a word, our study suggests that HPV infection is positively associated with the prevalence of RA in adults, and HPV immunization can reduce the prevalence of RA in adults. Of course, our findings need more powerful to prove these associations through rigorously designed prospective studies.